2011
DOI: 10.1007/s13337-011-0051-2
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Molecular Characterization of Two Distinct Tomato Strains of Cucumber mosaic virus Based on Complete RNA-3 Genome and Subgroup Specific Diagnosis

Abstract: Cucumber mosaic virus (CMV) is one of the most important viral pathogen infecting several plant species in India. Five isolates of CMV obtained from cucumber, muskmelon, tobacco and tomato from distinct geographical locations in India were analysed based on host-reactions and genome sequence. The majority of the isolates were very similar and only two isolates, Tfr-In and Tss-In showed distinct symptoms in tomato and high sequence diversity (77.8%) in coat protein (CP) gene. Tfr-In was isolated from tomato fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…RNA3 genome based characterization of three distinct tomato strains of CMV have been reported recently from India [8,26]. We further report, the biological and molecular characterization of CMV isolate retrieved from tomato which has closer affinity to European or East Asian CMV isolates than to other isolates previously characterized in India.…”
mentioning
confidence: 61%
“…RNA3 genome based characterization of three distinct tomato strains of CMV have been reported recently from India [8,26]. We further report, the biological and molecular characterization of CMV isolate retrieved from tomato which has closer affinity to European or East Asian CMV isolates than to other isolates previously characterized in India.…”
mentioning
confidence: 61%
“…Mainly, subgroup I isolates has been reported and there are few reports of subgroup II isolates [1,15,47,53]. The isolate under study showed up to 99 and 76 % similarity to the subgroup II and I isolates, respectively.…”
Section: Discussionmentioning
confidence: 82%
“…From India also there was report of mosaic symptoms on tomato by subgroup II strain [47] and now in a recent observation it was found that shoestring symptoms were not restricted to subgroup I. A subgroup II isolate Tss-In developed shoestring symptoms on tomato [15]. Cryoelectron microscopy of purified virus showed the presence of *28 nm isometric particle size, its SDS-PAGE and western blotting showed CP of *26 kDa and its dimeric form at *52 kDa.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The degree of CPRG downregulation followed the severity of chlorosis, indicating that CP mutations governed (directly or indirectly) the repression of CPRG mRNAs. The link of CP with symptoms seems to be strengthened with CMV isolates that were obtained from cucumber, muskmelon, tobacco, and tomato from distinct geographical locations in India (Swapna Geetanjali et al, 2011). The majority of the isolates were very similar but two isolates, Tfr-In and Tss-In showed distinct symptoms in tomato alongside the high sequence diversity in the CP gene.…”
Section: Cps and Virus Infectivity Pathogenicity And Symptom Expressionmentioning
confidence: 94%